Білім беру мазмұнын жаңартудың негізгі мəселелері - Базарбекова, Р. Ж. (My University, 2016)
There are enough actual social, cultural, environmental, economic and educational problems nowadays in Kazakhstan. Among them it is possible to distinguish the main problems in the field of education: unsystematic introduction of innovative technologies at school without criteria estimation of achievements of pupils; there is no aspiration to improve physical and psychological health of pupils and teachers; pupils’ functional illiteracy at school; a dissatisfaction of pupils with system of estimation of knowledge, etc. The reasons of updating of the maintenance of secondary education nowadays is possible to call the following requirements : the first prompt development of information technologies; secondly formation of functional literacy of pupils; in the third requirement of change of criteria estimation of achievements of pupils; in the fourth the actual need of introduction of new methods of training. In the conclusion of article as one of ways of improvement of quality of education and for close connection of teachers of high school and Higher education institutions is offered to introduce experience of world practice of using the Lesson Study technologies
Keywords: improvement of education content; functional literacy; criteria estimation; new methods of learning